HLA-B*44 allele associated with clinical parameters in HIV-1 infected Moroccan cohort - Youssoufi, Fatima; El Annaz, Hicham; Laraqui, Abdelilah; Tagajdid, Reda; Abi, Rachid; Elkochri, Safae; Frikh, Rachid; Bajjou, Tahar; Hjira, Naoufal; Sekhsokh, Yassine; Mrani, Saad (International Journal of Research in Medical Sciences, 2019)
Background: The human leukocyte antigen-B*44 (HLA-B*44) allele has been reported to have promising results in the control of human immunodeficiency virus-1 (HIV-1) infection and associated with protection against HIV-1 disease progression. In the Moroccan HIV-1 infected patients, the contribution of this allele has not been established. This study aimed to evaluate the distribution of HLA-B*44 allele among HIV-1-infected in Morocco. Additionally, investigate HLA-B*44 allele association with demographical and HIV clinical parameters. Methods: One hundred and sixty-seven HIV-1 infected, antiretroviral naive individuals were enrolled in this study. The HLA-B*44 allele screening was performed using the PCR amplification. Results: Of the 167 individuals genotyped, 26 (16%) of them expressing the HLA-B*44 allele. Clinical stages at diagnosis, median pre-treatment HIV viral load (pVL) and CD4 T cell counts differ significantly (p = 0.0001, p=0.001 and p=0.0001 respectively) between the patients who had been expressing the HLA-B*44 allele and patients who had not been expressing this allele. The presence of HLA-B*44 allele was significantly associated with pVL and CD4 T cell counts (p=0.004 and p=0.0001 respectively). The bivariate analysis has showed that the expression of the HLA-B*44 allele was strongly associated with advanced HIV infection (Odd ratio (OR) 0.12 (95% confidence interval (CI) 0.04-0.37), p=0.0001). Conclusions: Author have described for the first time in Morocco the association of the HLA-B*44 allele with the clinical parameters of HIV infection. These results expand the knowledge of the distribution and effect of this allele in the Moroccan population.